Research Paper : Wnt gene cluster in ventral ectoderm patterning of Drosophila embryo - Bahmani, Bozorgmehr; Joshi, Adita; Yadav, Prachi; Chandrasekaran, Shanti (The Indian Journal of Genetics and Plant Breeding, 2016)
Evolutionarily conserved gene clusters serve as important genomic assets and are exploited to elucidate primal designs of genome evolution. The quest to understand contemporary functional significance of such clusters underlying their persistent evolutionary selection is reasonable. One such gene cluster in Drosophila is the ‘Wnt cluster’ comprising of DWnt4-wg-DWnt6-DWnt10 on the left arm of the second chromosome.Wnts are secreted glycoproteins that work as cell signaling molecules and are involved in myriad of cellular,developmental processes and diseases like cancer. Wingless (wg) is prototype of this family along with other 6 Wnt genes reported in Drosophila melanogaster. Wingless (wg) functions during ventral epidermis patterning in embryo, wing morphogenesis etc. DWnt4 semi- lethal mutants are known in the context of cell motility in ovarian morphogenesis. However, no lethal mutations for DWnt4 are reported so far. Similarly, the understanding of potential biological roles of DWnt6 and DWnt10 remains elusive as no classical genetic alleles are reported. To fill this lacuna we have tried to decipher the plausible role of DWnt6 and DWnt10 in ectoderm patterning of embryo. Here we report that though DWnt6 and DWnt10 are not expressed in ventral ectoderm of embryo, they are able to rescue the defects in cuticles in absence of DWnt4 or wg. Similarly knockdown of DWnt6 and DWnt10 transcripts in DWnt4 and wg epidermal/ cuticular mutants resulted in increased defects in cuticles. These findings indicates that DWnt6 and DWnt10 can use canonical or non canonical Wnt pathway in absence of DWnt4 or wg and most probably they are using the same signaling mechanism in their natural function of domain which is yet to be known.